The body in culture, technology and society - Shilling, Chris (Theory, culture & society (Unnumbered), 2005)
This is a milestone in the sociology of the body. The Body in Culture, Technology and Society offers the most comprehensive overview of the field to date and an innovative framework for the analysis of embodiment. It is founded on a revised view of the relation of classical works to the body.